2021
DOI: 10.1186/s41747-021-00220-6
|View full text |Cite
|
Sign up to set email alerts
|

Material decomposition using iodine quantification on spectral CT for characterising nodules in the cirrhotic liver: a retrospective study

Abstract: Background There is limited scientific evidence on the potential of spectral computed tomography (SCT) for differentiation of nodules in the cirrhotic liver. We aimed to assess SCT-generated material density (MD) parameters for nodule characterisation in cirrhosis. Methods Dynamic dual-energy SCT scans of cirrhotic patients performed over 3 years were retrospectively reviewed. They were classified as hepatocellular carcinoma (HCC), regenerative or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…However, large-scale validation of this quantitative application seems necessary before broad clinical application can be implemented. The same applies to studies that suggested DECT-enabled differentiation of liver lesions, e. g., between small HCCs and metastases based on iodine quantification, which has been investigated only in small cohorts [59,60].…”
Section: Oncologic and Organ-specific Imagingmentioning
confidence: 97%
“…However, large-scale validation of this quantitative application seems necessary before broad clinical application can be implemented. The same applies to studies that suggested DECT-enabled differentiation of liver lesions, e. g., between small HCCs and metastases based on iodine quantification, which has been investigated only in small cohorts [59,60].…”
Section: Oncologic and Organ-specific Imagingmentioning
confidence: 97%